A mass spectrometric investigation on some 5-substituted adamantan-2-ones. Issue 3 (1997) - Martínez Martínez, Roberto Roberto; Cetina Cetina, Raúl Raúl; Jiménez Jiménez, Federico Federico; Velasco Velasco, Luis Luis; Pérez Pérez, Javier Javier
Abstract : The mass spectrometric behavior of a series of 5-substituted adamantan-2-ones has been studied in different ionization conditions (Electron Ionization and Fast Atom Bombardment), with the aid of linked scan experiments.